Determining Achievement Scholarship Recipients Using the Simple Additive Weighting Method: Penentuan Penerima Beasiswa Prestasi Menggunakan Metode Simple Additive Weighting - Dwi Ramadani, Vira (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2023)
SMA Negeri 1 Koto Salak is one of the school institutions that provides scholarships to its students. However, the determination of scholarship recipients is still done by collecting or viewing the scholarship registration file, which consists of the average value of the report card, the number of siblings, active in the organization and the economically disadvantaged. So that the school is difficult to determine the priority of which students are entitled to a scholarship because of the large number of scholarship applicants. This study aims to analyze, design and build a Decision Support System for receiving merit scholarships using the Simple Additive Weighting method. This method is the method used in finding the weighted sum of the performance ratings on each alternative, in this case those who are entitled to receive scholarships based on the recipient criteria. With this, the assessment will be more accurate because it is based on predetermined criteria and weights.